Enlightenment Bible : Translation, Scholarship, Culture. - Sheehan, Jonathan (Princeton University Press, 2013)
How did the Bible survive the Enlightenment? In this book, Jonathan Sheehan shows how Protestant translators and scholars in the eighteenth century transformed the Bible from a book justified by theology to one justified by culture. In doing so, the Bible was made into the cornerstone of Western heritage and invested with meaning, authority, and significance even for a secular age. The Enlightenment Bible offers a new history of the Bible in the century of its greatest crisis and, in turn, a new vision of this century and its effects on religion. Although the Enlightenment has.